Concept of Decorative Variety of Wood Carvings in the Princely Within the Framework of Functional Aesthetic Theory - Rahayu Adi Prabowo; Guntur Guntur; Sunarmi Sunarmi (International Journal Labs, 2025)
This study examines the concept of the application of a variety of decorative wood carvings in the Ndalem Keprieranan through the perspective of functional aesthetic theory. This study aims to identify the connection between aesthetic aspects, functions, and philosophical values contained in wood carving elements in traditional Javanese architecture. The variety of ornaments on the ndalem building acts as a decorative motif that contains symbolic meaning that represents the value system, social structure, and life view of the Javanese people about the relationship between humans, nature, and God. The research method uses a descriptive qualitative approach through visual observation, documentation, and literature studies, with analysis focused on the shape, motif, composition, and symbolic function of carving. The results of the study suggest that the application of functional aesthetics in the variety of decorative wood carvings in the palace displays a harmonious harmony between visual beauty and constructive function. The value of Tata-Titi-Teges is reflected in the regularity of form, the accuracy of proportion, and the firmness of symbolic meaning, while the value of Nata-Niti-Natas shows a reflective and spiritual dimension that directs human consciousness towards the order of the cosmos. Overall, this study emphasizes that traditional Javanese aesthetics are oriented towards the beauty of appearance which is a value system that combines visual, functional, and spiritual principles in an integrated manner, which makes the variety of wood carvings as an expression of harmony between material and immaterial aspects in the life of the Javanese people.